Question
upstudy study bank question image url

3 WITHOUT using a calculator, show that \( \frac{9-\sqrt{54}}{6 \sqrt{2}} \) is equal to \( \frac{3 \sqrt{2}-2 \sqrt{3}}{4} \).

Ask by Bob Colon. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\(\frac{9 - \sqrt{54}}{6 \sqrt{2}} = \frac{3 \sqrt{2} - 2 \sqrt{3}}{4}\).

Solution

To show that \[ \frac{9 - \sqrt{54}}{6 \sqrt{2}} = \frac{3 \sqrt{2} - 2 \sqrt{3}}{4}, \] let's simplify the left-hand side (LHS) step by step without using a calculator. 1. **Simplify \(\sqrt{54}\):** \[ \sqrt{54} = \sqrt{9 \times 6} = 3 \sqrt{6}. \] 2. **Substitute \(\sqrt{54}\) back into the LHS:** \[ \frac{9 - \sqrt{54}}{6 \sqrt{2}} = \frac{9 - 3 \sqrt{6}}{6 \sqrt{2}}. \] 3. **Factor out a 3 from the numerator:** \[ \frac{9 - 3 \sqrt{6}}{6 \sqrt{2}} = \frac{3(3 - \sqrt{6})}{6 \sqrt{2}} = \frac{3 - \sqrt{6}}{2 \sqrt{2}}. \] 4. **Rationalize the denominator by multiplying the numerator and denominator by \(\sqrt{2}\):** \[ \frac{3 - \sqrt{6}}{2 \sqrt{2}} \times \frac{\sqrt{2}}{\sqrt{2}} = \frac{(3 - \sqrt{6}) \sqrt{2}}{2 \times 2} = \frac{3 \sqrt{2} - \sqrt{6} \sqrt{2}}{4}. \] 5. **Simplify \(\sqrt{6} \times \sqrt{2}\):** \[ \sqrt{6} \times \sqrt{2} = \sqrt{12} = 2 \sqrt{3}. \] 6. **Substitute back into the expression:** \[ \frac{3 \sqrt{2} - 2 \sqrt{3}}{4}. \] Thus, we've shown that \[ \frac{9 - \sqrt{54}}{6 \sqrt{2}} = \frac{3 \sqrt{2} - 2 \sqrt{3}}{4}. \] **Answer:** After simplifying, both expressions equal (3√2 – 2√3) divided by four. Thus, \(\frac{9-\sqrt{54}}{6 \sqrt{2}} = \frac{3 \sqrt{2}-2 \sqrt{3}}{4}\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To show that \( \frac{9-\sqrt{54}}{6 \sqrt{2}} = \frac{3 \sqrt{2}-2 \sqrt{3}}{4} \), we will simplify the left-hand side. Starting with \( \sqrt{54} \): \[ \sqrt{54} = \sqrt{9 \cdot 6} = \sqrt{9} \cdot \sqrt{6} = 3\sqrt{6} \] Substituting this back into the left-hand side gives: \[ \frac{9 - \sqrt{54}}{6 \sqrt{2}} = \frac{9 - 3\sqrt{6}}{6 \sqrt{2}} \] Now we can split the fraction: \[ = \frac{9}{6 \sqrt{2}} - \frac{3\sqrt{6}}{6 \sqrt{2}} = \frac{3}{2\sqrt{2}} - \frac{\sqrt{6}}{2\sqrt{2}} \] Next, let's simplify \(\frac{3}{2\sqrt{2}}\) and \(\frac{\sqrt{6}}{2\sqrt{2}}\): \[ \frac{3}{2\sqrt{2}} = \frac{3\sqrt{2}}{4} \] \[ \frac{\sqrt{6}}{2\sqrt{2}} = \frac{\sqrt{6}}{\sqrt{2} \cdot 2} = \frac{\sqrt{6}}{\sqrt{2}} \cdot \frac{1}{2} = \frac{\sqrt{3} \cdot \sqrt{2}}{\sqrt{2}} \cdot \frac{1}{2} = \frac{\sqrt{3}}{2} \] Thus, combining these results: \[ \frac{3}{2\sqrt{2}} - \frac{\sqrt{6}}{2\sqrt{2}} = \frac{3\sqrt{2}}{4} - \frac{\sqrt{3}}{2} \] Thankfully, we can express \(\frac{\sqrt{3}}{2}\) with a common denominator: \[ = \frac{3\sqrt{2}}{4} - \frac{2\sqrt{3}}{4} = \frac{3\sqrt{2} - 2\sqrt{3}}{4} \] Finally, we see that the two sides are equal: \[ \frac{9-\sqrt{54}}{6 \sqrt{2}} = \frac{3\sqrt{2}-2\sqrt{3}}{4} \] Therefore, we have shown that \( \frac{9-\sqrt{54}}{6 \sqrt{2}} \) is indeed equal to \( \frac{3 \sqrt{2}-2 \sqrt{3}}{4} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy